Komodifikasi Makna Tenun Gringsing sebagai “Soft Power” Menghadapi Budaya Global - I Nyoman Lodra (Pusat Kajian Bali Universitas Udayana, 2016)
Abstract Tenun Gringsing (Gringsing woven cloth) is a craft made of colored cotton yarn with weaving technique. The woven fabric is in the form of cloth sheet with various sizes, colors, and motifs. Tenun Gringsing is commonly called double ikat, which is the landmark of Tenganan Pegringsingan village. The woven cloth functions as a ritual medium in customary, religious, and marital activities inherited from their ancestors. Commodification with creative touch creating a product with new meanings emerges as the influence of modernization. It causes the shift of values from sacred to secular ones, which has soft power. It is marked by the change of the cloth’s function from ritual purposes to fashion, which still upholds local values possessing cultural force ensuring victory in the global competition. The research used commodification and the main theory. The location of the study is Tenganan Pegringsingan village, Karangasem, Bali. It is a qualitative descriptive study with ethnographic and historical approaches. The data were collected by observing the use of Tenun Gringsing, interviewing relevant informants including crafters, community leaders, merchants, and tourists. In conclusion, the commodification of the cloth’s meaning is the villagers’ openness to global culture. Keyword: Tenun Gringsing, landmark, creative field, commodification, soft power, global culture